Standards and Local Curriculum: A Zero-Sum Game? - Nancy E. Jennings (Journal of Research in Rural Education, 2000)
Many rural educators and researchers have not embraced standards-based reform warmly. Some are wary ofstandards driving out unique and locally responsive curriculum. Others cast standards as one more example ofa reform largely geared toward urban and suburban schools but foisted on rural schools regardless of applicability. These arguments are mostly rhetorical. Few studies have looked at the effects ofstandards' implementation on the classroom practices ofrural educators. In this paper, I examine the impact ofa state standards-based reform, the Maine Learning Results, on curriculum and instruction infour rural schools. Ifocus on the impact that standards have on locally responsive curriculum in the schools. I suggest that state standards and locally responsive curriculum ultimately may not be as incompatible as many scholars and practitioners suggest.